Draft Annual Plan 1975-76 Administration of the Union Territory of Dadra and Nagar Haveli - Planning Commission (Planning Commission, 1975)
Dadra and Nagar Haveli is a small Union Territory about 490 sq.K.M. in area situated about 110 miles north of Bombay and bounded by the Bulsar and Thana Districts of Gujarat and Maharashtra. the population according to 1971 census is 74165 of which 88% belong to the scheduled tribes. Forest area covers nearly 42% of the territory and about 25000 hectares are under cultivation. Generally speaking, the territory is poor and backward and the tribal population is almost entirely engaged in agriculture or agricultural labour.
Administration of the Union Territory of Dadra and Nagar Haveli